2020
DOI: 10.1111/jocd.13301
|View full text |Cite
|
Sign up to set email alerts
|

In vitro human skin concentrations following topical application of 2% tranexamic acid in co‐enhancer cream and branded cream formulations

Abstract: Background Melasma is a common pigmentary disorder that responds well to treatment with oral and/or locally injected tranexamic acid but less so to topical application. We hypothesized that this may be due to an inability of some topical formulations of tranexamic acid to achieve robust therapeutic concentrations at the viable epidermal target site in the skin. Aims To measure in vitro human epidermal and dermal skin concentrations of tranexamic acid following topical application of Fairence® T‐Complex, co‐enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The improvement of skin penetration efficacy is an essential factor in the skincare efficacy of cosmetics 33,34 . Previous studies reported that ion‐pairing with counter ions enhances the skin permeability by increased lipophilicity of a molecule 23,35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of skin penetration efficacy is an essential factor in the skincare efficacy of cosmetics 33,34 . Previous studies reported that ion‐pairing with counter ions enhances the skin permeability by increased lipophilicity of a molecule 23,35 .…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of skin penetration efficacy is an essential factor in the skincare efficacy of cosmetics. 33,34 Previous studies reported F I G U R E 1 Viscosity (A) and conductivity (B) changes in ion-pairing between serine and arginine at various molar ratios. Each sample was measured at 25°C.…”
Section: Enhanced Permeability and Exfoliation Efficacy By Ion-pairingmentioning
confidence: 99%
“…It is hypothesized that a more robust and timely clinical response with this formulation may be achieved, especially in refractory patients. 18 An in vitro human skin penetration study shows that this formula significantly enhances the penetration of TXA into the skin vs regular TXA cream formula. It achieved an 11-fold increase in penetration of TXA to the targeted site vs the nonenhanced product (ie, at 24 hours, this TXA formulation achieved a concentration of 43.9 µg/mL vs 3.9 µg/mL at the epidermis, and 1.57 µg/mL vs 0.14 µg/mL at the dermis, respectively).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…It achieved an 11-fold increase in penetration of TXA to the targeted site vs the nonenhanced product (ie, at 24 hours, this TXA formulation achieved a concentration of 43.9 µg/mL vs 3.9 µg/mL at the epidermis, and 1.57 µg/mL vs 0.14 µg/mL at the dermis, respectively). 18 This formulation tended to reach similar peak plasma levels as orally administered TXA based on pharmacokinetic study results (ie, maximal inhibitory concentration values of TXA fibrinolytic activity are <20.0 μg/mL or within the epidermal concentration range). 18 Clinical studies have demonstrated a significant reduction in the melasma area and severity index (MASI) of 37% compared with baseline and improvement in skin clarity in both pigmented and normal skin.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…(ii) Franz cell (diffusion cell) consists of a donor compartment (chamber for drug or active application), a fragment of skin or a membrane simulating skin within which the drug or active may diffuse, and an acceptor chamber containing an appropriate dosage solution from which molecules of interest can be quantified. [16][17][18][19] The passage kinetics is determined by dosing the active substance, at regular intervals, in the acceptor compartment. It is used for toxicity screening or quality control.…”
Section: Introductionmentioning
confidence: 99%